The depressogenic potential of added dietary sugars. (January 2020) - Reis, Daniel J.; Ilardi, Stephen S.; Namekata, Michael S.; Wing, Erik K.; Fowler, Carina H.
Abstract: Added sugars are ubiquitous in contemporary Western diets. Although excessive sugar consumption is now robustly associated with an array of adverse health consequences, comparatively little research has thus far addressed its impact on the risk of mental illness. But ample evidence suggests that high-dose sugar intake can perturb numerous metabolic, inflammatory, and neurobiological processes. Many such effects are of particular relevance to the onset and maintenance of depressive illness, among them: systemic inflammation, gut microbiota disruption, perturbed dopaminergic reward signaling, insulin resistance, oxidative stress, and the generation of toxic advanced glycation end-products (AGEs). Accordingly, we hypothesize that added dietary sugars carry the potential to increase vulnerability to major depressive disorder, particularly at high levels of consumption. The present paper: (a) summarizes the existing experimental and epidemiological research regarding sugar consumption and depression vulnerability; (b) examines the impact of sugar ingestion on known depressogenic physiological processes; and (c) outlines the clinical and theoretical implications of the apparent sugar-depression link. We conclude that the extant literature supports the hypothesized depressogenic impact of added dietary sugars, and propose that an improved understanding of the effects of sugar on body and mind may aid in the development of novel therapeutic and preventative measures for depression.